2008
DOI: 10.1161/circ.118.suppl_18.s_1446-c
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 8: Influence of Receiving Hospital Characteristics on Survival after Cardiac Arrest

Abstract: Hospital management of out-of-hospital cardiac arrest (OHCA) patients after return of spontaneous circulation (ROSC) can influence patient survival via interventions such as hypothermia and cardiac catheterization (CATH). This study tested the hypothesis that survival differed between different types of hospitals for subjects with ROSC after OHCA. Methods: Adult (≥ 18 years) subjects with paramedic-documented ROSC or who lived >1 day after OHCA were identified with their receiving hospital in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…154 There were 10 observational studies that compared OHCA patient survival outcomes between hospitals based on various hospital characteristics such as hospital type, hospital size, hospital location, and OHCA case volume. [155][156][157][158][159][160][161][162][163][164] Six observational studies compared OHCA patient survival outcomes before and after the implementation of a regionalized system of postresuscitation care. [165][166][167][168][169][170] Six observational studies compared patient…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…154 There were 10 observational studies that compared OHCA patient survival outcomes between hospitals based on various hospital characteristics such as hospital type, hospital size, hospital location, and OHCA case volume. [155][156][157][158][159][160][161][162][163][164] Six observational studies compared OHCA patient survival outcomes before and after the implementation of a regionalized system of postresuscitation care. [165][166][167][168][169][170] Six observational studies compared patient…”
Section: Consensus On Sciencementioning
confidence: 99%
“…154 For the important outcome of survival, we identified very-low-quality evidence (downgraded for significant risk of bias and indirectness, with heterogeneity in reported hospital factors associated with differences in patient survival) from 21 studies with more than 120 000 patients. Three studies examined survival at 30 days, 159,161,173 18 studies with more than 120 000 patients reported survival to hospital discharge, [155][156][157][158][159][160]163,164,166,[168][169][170][171][172][174][175][176] and 1 study reported survival at 4.6 years. 162 There was an association with survival and transport to a cardiac arrest center; however, the specific hospital factors most related to patient outcome were inconsistent in these studies.…”
Section: S254 Circulationmentioning
confidence: 99%